Growth, Urbanization, and Poverty Reduction in India - Datt, Gaurav; Ravallion, Martin; Murgai, Rinku (World Bank, Washington, DC, 2016)
Longstanding development issues are revisited in the light of a newly-constructed data set of poverty measures for India spanning 60 years, including 20 years since reforms began in earnest in 1991. The study finds a downward trend in poverty measures since 1970, with an acceleration post-1991, despite rising inequality. Faster poverty decline came with higher growth and a more pro-poor pattern of growth. Post-1991 data suggest stronger inter-sectoral linkages: urban consumption growth brought gains to the rural as well as the urban poor, and the primary-secondary-tertiary composition of growth has ceased to matter, as all three sectors contributed to poverty reduction.